2021
DOI: 10.1055/s-0040-1718780
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Treatment Outcomes of Head Injury in Bangladesh: Perspective from the Largest Tertiary Care Hospital

Abstract: Background Traumatic brain injury (TBI) is one of the leading causes of mortality and morbidity. Economic impact is much worse in developing countries like Bangladesh, as victims are frequently male, productive, and breadwinners of the families. Objectives The objective of our study was to highlight the etiological pattern and distribution of varieties of head injuries in Bangladesh and give recommendations regarding how this problem can be solved or reduce to some extent at least. Methods From January 2017 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Nath et al 23 also found that males contributed to a major part of the fraction amongst the injured (98.0%), and most patients (36.0%) were in 3 rd decade of their life. Das et al 22 also found, male-to female ratio was found to be 2.57(72%):1 (28%). Another study 19 shows male-to-female ratio of 4.6:1, which does not correlate with our observation probably due to presence of more female workers like garment workers and day laborers in the community.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Nath et al 23 also found that males contributed to a major part of the fraction amongst the injured (98.0%), and most patients (36.0%) were in 3 rd decade of their life. Das et al 22 also found, male-to female ratio was found to be 2.57(72%):1 (28%). Another study 19 shows male-to-female ratio of 4.6:1, which does not correlate with our observation probably due to presence of more female workers like garment workers and day laborers in the community.…”
Section: Discussionmentioning
confidence: 85%
“…Some authors have reported that the most frequent lesions in mild TBI were subgaleal and palpebral hematomas, fractures and cerebral contusions, others described craniofacial fractures as the most frequent lesions, and one study demonstrated the prevalence of cerebral contusions (26.8%), extradural hematomas (6.8%), subarachnoid hemorrhage (5.7%) and subdural hematomas (4.4%) in patients with mild traumatic brain injury 26 . Das et al 22 found on the basis of CT-scan of head, diagnoses of traumatic brain injury were AEDH in 42.3% (1,974) cases, depressed skull fracture in 28.9% cases, ASDH in 12.3% cases, brain contusion in 10.20% (476) cases, and SAH or combination in 6.34% (296) cases of the total study population. It was found that 58.0% patients were normal cognition, 22.0% cases were mild cognitive impairment, 17.62% cases were moderate cognitive impairment and only 2.0% were severe cognitive impairment during discharge.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations